Opportunity recognition in immigrant entrepreneurship through social capital and geographical proximity: a conceptual framework - Nurul Atasha Jamaludin; Zizah Che Senik; Hamizah Abd Hamid; Nur Sa'adah Muhamad (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this paper is to present a conceptual framework of the role of social capital as an ultimate resource for immigrant entrepreneurs in recognising entrepreneurial opportunities. Research consistently reveals that immigrants have higher tendency to engage in entrepreneurial activities in countries where they reside. Based on a review of existing literature, resources such as human, social, and financial capital facilitate immigrants to pursue entrepreneurial activities. In recognising business opportunities, social contexts have immensely influenced the entrepreneurial process. However, the role of social capital as an ultimate resource for immigrant entrepreneurship have yet to be comprehensively understood. Social capital is significantly related to the information flows, the trust and norms between individuals. Additionally, the geographical proximity between immigrants and their co-ethnic groups and local communities which enable more rigorous social exchanges plays prevalence role for immigrants to pursue entrepreneurial activities. Therefore, we could argue that the social capital and immigrant entrepreneurs’ geographical proximity are crucial constructs for immigrant entrepreneurs to recognise opportunities for their business ventures in a host country. The review of past literature enables us to develop a conceptual framework on how social capital and geographical proximity may assist the opportunity recognition of immigrant entrepreneurs. The proposed conceptual framework offers three general propositions than can be empirically validated in future research. This paper contributes to enhance the understanding of immigrant entrepreneurship from the lens of opportunity recognition, social capital and geographical proximity.